Earth Friendly Computation: Applying Indigenous Data Lifecycles in Medical and Sovereign AI - Fox, Keolu; Tsosie, Krystal; Ioannidis, Alex; Wasik, Kaja; Calac, Alec; Dawson, Eric (Pacific Symposium on Biocomputing. Pacific Symposium on Biocomputing, 2025)
The following sections are included: Overview, Background & key terms, Earth Friendly Computation 574: Indigenous Data Sovereignty, Circular Systems, and Solarpunk Solutions for a Sustainable Future, AI in Point-of-Care: A Sustainable Healthcare Revolution at the Edge, Conclusion: The Future of Earth Friendly Computation, Acknowledgments, References.